Types of Adult Attention-Deficit/Hyperactivity Disorder: A Replication Analysis - Reimherr, Frederick W; Roesler, Michael; Marchant, Barrie K; Gift, Thomas E; Retz, Wolfgang; Philipp-Wiegmann, Florence; Reimherr, Matthew L (The journal of clinical psychiatry, 2020)
Research supports the importance of emotional symptoms in adults with attention-deficit/hyperactivity disorder (ADHD), which are not reflected in the DSM-5 or ICD-10 criteria. The Wender-Reimherr Adult Attention Deficit Disorder Scale (WRAADDS) assesses these symptoms, plus inattention, hyperactivity, and impulsivity. This scale allowed us to divide adult ADHD into 2 subtypes in a 2015 publication: ADHD inattentive presentation and ADHD emotional dysregulation presentation. The present study refines this observation using a larger, more diverse sample. Eight double-blind adult ADHD clinical trials (encompassing 1,490 subjects) were selected because they included assessment with the WRAADDS; a second, alternative ADHD measure; and the Clinical Global Impressions-Severity of Illness scale (CGI-S). These data were subjected to confirmatory factor analyses, and ADHD presentations were compared, including treatment response. The original factor structure fit poorly with these new data. However, an alternative 2-factor solution fit both the original and the new subjects. ADHD inattentive presentation (n = 774) was defined by the inattention factor, and ADHD emotional dysregulation presentation (n = 620) was defined by additional elevation of the emotional dysregulation factor. The proportion of ADHD emotional dysregulation presentation ranged from 25% to 73% across the 8 studies. The emotional dysregulation presentation was associated with both a greater severity as measured by the CGI-S (P < .001) and more manifestations of childhood ADHD as measured by the Wender Utah Rating Scale (P < .001). Factor analytic results supported the validity of 2 adult ADHD presentations based on levels of emotional dysregulation. This system offers a more clinically relevant approach to the diagnosis of ADHD in adults than does the DSM system.